Analysis of bone marrow supernatant neutrophil gelatinase‐associated lipocalin and hematological parameters in hematological malignancy. Issue 6 (24th February 2020) - Cho, Chi‐Hyun; Cha, Jaehyung; Chang, Eun‐Ah; Nam, Myung‐Hyun; Park, Seo‐Jin; Sung, Hwa Jung; Lee, Se Ryeon
Abstract: Background: Neutrophil gelatinase‐associated lipocalin (NGAL) is a urine biomarker related to acute renal injury. Whereas several studies have evaluated NGAL levels in hematological malignancy, using peripheral blood (PB). Recently, bone marrow (BM) NGAL level was reported to be higher than PB NGAL level in individuals with hematological malignancy, suggesting that BM NGAL would reflect BM microenvironment better than PB NGAL. We measured BM NGAL levels in patients with hematological malignancy, comparing those with NGAL levels in normal BM. We evaluated the association of BM NGAL with hematological parameters including neutrophil counts. Methods: BM samples were collected from 107 patients who underwent BM examination. Immunoassays were used to assess NGAL levels. Data on hematological parameters were collected from medical records. Intergroup comparisons were performed using the Kruskal‐Wallis H test and Pearson chi‐square test. Single and multiple regression analyses were performed to analyze the relationships. Results: The independent factors that affected the BM NGAL level were neutrophil counts and BM band neutrophil%, while neutrophil count was the main influencing factor. The acute myeloid leukemia (n = 18) and myelodysplastic syndrome (n = 25) groups showed statistically lower BM NGAL levels than patients with normal BM. The myeloproliferative neoplasm group (n = 34) showed higher BM NGAL levels than patients with normal BM, but this difference was not statistically significant. Neutrophil counts and BM band neutrophil% showed intergroup patterns similar to those of BM NGAL levels. Conclusion: BM NGAL was related to neutrophil count and BM band neutrophil%, showing different levels according to hematological malignant disease entities.